1999
DOI: 10.1111/0020-8833.00130
|View full text |Cite
|
Sign up to set email alerts
|

The Role of "Enemy Images" and Ideology of Elite Belief Systems

Abstract: We use data from the Leadership Opinion Project (LOP), a panel survey of American opinion leaders which brackets the end of the Cold War, to investigate two interrelated questions about the structure of elites' foreign policy beliefs. We assess, first, whether the militant internationalism/cooperative internationalism scheme, developed primarily by Wittkopf (1981, 1990) and Holsti and Rosenau (1990), has continued relevance now that the USSR has collapsed; and second, whether Hurwitz and Peffley's (1987, 1990;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 48 publications
0
17
0
Order By: Relevance
“…Ideology, however, represents something more than a set of beliefs about what is right. Rather, ideology entails an integrated set of values and goals that assume unique status in which attainment of salient goals, or failure to attain these goals, is held to be determined by a fixed, relatively rigid, set of beliefs about the causes influencing goal attainment and failures in goal attainment (Murray & Cowden, 1999). In other words, ideology involves a mental model specifying desirable goals and the causes shaping goal attainment (Strange & Mumford, 2005).…”
Section: Ideological Groupsmentioning
confidence: 99%
“…Ideology, however, represents something more than a set of beliefs about what is right. Rather, ideology entails an integrated set of values and goals that assume unique status in which attainment of salient goals, or failure to attain these goals, is held to be determined by a fixed, relatively rigid, set of beliefs about the causes influencing goal attainment and failures in goal attainment (Murray & Cowden, 1999). In other words, ideology involves a mental model specifying desirable goals and the causes shaping goal attainment (Strange & Mumford, 2005).…”
Section: Ideological Groupsmentioning
confidence: 99%
“…Ole Holsti () offers a clue. Research on the structure of American foreign policy opinion has found that two major dimensions structure most of mass and elite attitudes on international affairs in the United States (Holsti and Rosenau , ; Wittkopf ; Murray ; Murray and Cowden ; Rathbun ). Holsti, along with his coauthor Jim Rosenau, argues that particular combinations of these two attitude clusters, militant internationalism (MI) and cooperative internationalism (CI), allow for the construction of a fourfold typology (1988).…”
Section: Linking Qualitative and Quantitative Research On Foreign Polmentioning
confidence: 99%
“…In other articles (Rathbun ), I call this “hierarchy,” Chittick, Billingsley and Travis () “militarism” and Nincic and Ramos () a “negative incentives‐based means of policy.” Questions typically used to capture this latent variable evoke the discussion above. Militant internationalists believe that “rather than simply countering our opponent's thrusts, it is necessary to strike at the heart of an opponent's power.” An embrace of the importance of a strong reputation is evident in a belief that “there is considerable validity in the ‘domino theory’ that when one nation falls to aggressor nations, others nearby will soon follow a similar path” (Holsti and Rosenau , ; Wittkopf ; Murray ; Murray and Cowden ; Rathbun ).…”
Section: Linking Qualitative and Quantitative Research On Foreign Polmentioning
confidence: 99%
See 1 more Smart Citation
“…Sobel (2001) explains these categories in the following light: internationalists favor both conciliatory and conflict strategies, accommodationists embrace cooperative internationalism, hardliners take a militant internationalist approach, and isolationists reject internationalism and most U.S. activity not directly relevant to the country's survival. Murray and Cowden (1999) adjusted the observed variables used by Holsti and Rosenau's approach in removing most of the USSR‐related variables and substituting more general militarism and oppressor questions. Holsti (1996) suggests that liberals tend to be accommodationists and are unsupportive of militant internationalism, while conservatives are internationalists or hardliners who perceive the world as conflictual and will respond with military force when necessary.…”
Section: The Eaglesmentioning
confidence: 99%